M2M Communications in the Smart Grid: Applications, Standards, Enabling Technologies, and Research Challenges. (4th August 2011) - Tan, Siok Kheng; Sooriyabandara, Mahesh; Fan, Zhong
Abstract : We present some of the ongoing standardisation work in M2M communications followed by the application of machine-to-machine (M2M) communications to smart grid. We analyse and discuss the enabling technologies in M2M and present an overview of the communications challenges and research opportunities with a focus on wireless sensor networks and their applications in a smart grid environment.